2013
DOI: 10.1159/000352095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tadalafil on Hemorrhagic Cystitis and Testicular Dysfunction Induced by Cyclophosphamide in Rats

Abstract: Introduction: The protective and/or therapeutic potential of tadalafil (TDL) on cyclophosphamide (CP)-induced hemorrhagic cystitis (HC) and testicular dysfunction in rats was evaluated. Materials and Methods: The animals except from the control group were divided into four groups and treated with saline, or 1, 5 or 10 mg/kg TDL orally (CP, TDL1, TDL5 and TDL10 groups, respectively) before and after CP injection. Body and organ weights, sperm count, cGMP, nitric oxide (NO), IL-6 and IL-10 levels in serum and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It is known that cyclophosphamide triggers an inflammatory reaction in animals with different mechanisms. Cytokines (42,(44)(45)(46) and PPARγ pathway (47) are thought to play a role in these proinflammatory events.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cyclophosphamide triggers an inflammatory reaction in animals with different mechanisms. Cytokines (42,(44)(45)(46) and PPARγ pathway (47) are thought to play a role in these proinflammatory events.…”
Section: Discussionmentioning
confidence: 99%
“…CP group: Animals received 0.2 mL saline i.p for 7 consecutive days, before and after CP (Eczacibasi, Turkey) injection (200 mg/kg ip). 12 , 13 …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Spitzer et al have reported that the PDE-5 inhibitor sildenafil increased estradiol levels in 40 men (ages 40-70 years) with ED, despite increasing testosterone levels [89]. Additionally, several reports have demonstrated that PDE-5 inhibitors increase testosterone levels [90][91][92][93][94][95][96]. When testosterone is low, estradiol levels may also be low because testosterone is metabolized to estradiol by aromatase.…”
Section: Ed Treatment and Estrogenmentioning
confidence: 99%